2020
DOI: 10.3390/cells9040915
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps (NETs) Take the Central Stage in Driving Autoimmune Responses

Abstract: Following fifteen years of research, neutrophil extracellular traps (NETs) are widely reported in a large range of inflammatory infectious and non-infectious diseases. Cumulating evidences from in vitro, in vivo and clinical diagnostics suggest that NETs may play a crucial role in inflammation and autoimmunity in a variety of autoimmune diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV). Most likely, NETs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 150 publications
(170 reference statements)
2
146
0
7
Order By: Relevance
“…In addition, it was found that NETs engulfed by fibroblasts stimulated formation of the antibodies against citrullinated histones in the RA model [ 105 ]. Similar observations indicate involvement of NETosis in the autoimmune diseases, such as vasculitis associated with “anti-neutrophil antibodies” (AAV), antiphospholipid syndrome, multiple sclerosis, and psoriasis (see review [ 106 ]). Interestingly, in some diseases, NETosis can play an anti-inflammatory role.…”
Section: The Role Of Netosis In Host Defence and Pathologymentioning
confidence: 61%
“…In addition, it was found that NETs engulfed by fibroblasts stimulated formation of the antibodies against citrullinated histones in the RA model [ 105 ]. Similar observations indicate involvement of NETosis in the autoimmune diseases, such as vasculitis associated with “anti-neutrophil antibodies” (AAV), antiphospholipid syndrome, multiple sclerosis, and psoriasis (see review [ 106 ]). Interestingly, in some diseases, NETosis can play an anti-inflammatory role.…”
Section: The Role Of Netosis In Host Defence and Pathologymentioning
confidence: 61%
“…Initially, most of studies were focused on microorganisms-triggered NETs. As a vast number of molecules were identi ed as NETs stimuli such as ionomycin [34], nicotine [35], hydrogen peroxide [11], TNF-α [36], Fc receptors [13], IFN-γ [37], and antimicrobial peptides [38], increasing studies are paying attention on non-infectious and autoimmune diseases [39,40]. Histamine is a main mediator in allergic diseases, and we found it also can induce NET formation.…”
Section: Discussionmentioning
confidence: 78%
“…Consistent with this, Fousert et al also propose NETs as promising biomarkers for autoimmune diseases since they contribute to the development of autoimmunity by breaking self-tolerance [22]. They further conclude that therapeutics targeted at neutrophils and NETs will be beneficial for the treatment of inflammatory autoimmune diseases [22].…”
Section: Neutrophils and Nets In Sterile Inflammationmentioning
confidence: 87%